Sensory characteristics and fatty acid composition of Raschera PDO cheese according to the production system - Giaccone D.; Coppa M.; Revello-Chion A.; Galassi L.; Bianchi P.; Tabacco E.; Borreani G. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
The Raschera is a PDO semi-cooked and pressed cheese made from partially skimmed milk, which is produced within the Cuneo Province, in North-West Italy. Aiming to explore the widest variation in production conditions and cheesemaking technology, twenty Raschera cheeses were sampled (ten in winter, W; and ten in summer, S) from ten dairy plant producing almost all of the total PDO Raschera cheese production. The cheeses were divided in three production systems: (i) raw milk (IR) or (ii) pasteurized milk (IP) cheeses from intensive farming system, feeding cows mainly on maize silage and concentrates, and (iii) raw milk cheese from extensive farming system (ER), feeding cows mainly with hay in winter or fresh herbage in summer. The principal component analysis (PCA) performed on sensory attributes clearly separate summer from winter cheeses, the first being characterized by stronger notes. Within summer cheeses, ER were clearly separated from IP and IR cheeses, being the ER cheeses characterized by stronger, herbaceous and vegetables notes, and the IP and IR by more cream and butter notes. The FA composition of the cheeses also allowed to a similar differentiation, but the separation between the season was evident only for ER system. The research highlighted that the sensory properties and FA composition of Raschera PDO cheese depend on the production system and on its seasonal variations.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)